If you give a moose a muffin - Numeroff, Laura Joffe; Bond, Felicia ([New York] : Laura Geringer Book, 1994)
Chaos can ensue if you give a moose a muffin and start him on a cycle of urgent requests.
"Ages 3 to 7"--Cover p. [4].
School Library Journal
School Library Journal starred
2.7
K-3.
K-3
Keywords: Oversize books -- Specimens; Moose -- Fiction; Oversize books; Big books; Moose -- Fiction